Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.1007/s10620-018-5257-3
|View full text |Cite
|
Sign up to set email alerts
|

A Survey of Expert Practice and Attitudes Regarding Advanced Imaging Modalities in Surveillance of Barrett’s Esophagus

Abstract: These results should inform benchmarks that need to be met for guidelines to recommend the routine use of AIMs in the surveillance of BE patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…This threshold was partly based on a recent study among a group of international BE experts who reported the minimum incremental diagnostic yield for the use of advanced imaging techniques in BE surveillance. 91 In this study, experts reported a minimum incremental increase in the diagnostic yield of 27% (interquartile range, 20%-50%) for CLE before implementation in clinical practice. Furthermore, the 4 RCTs had a prevalence of dysplasia ranging from 19% to 35%, much higher than the prevalence of dysplasia in the BE population seen by most gastroenterologists at nonspecialized centers.…”
Section: Question 4: In Patients With Be Undergoing Endoscopy For Surmentioning
confidence: 69%
See 2 more Smart Citations
“…This threshold was partly based on a recent study among a group of international BE experts who reported the minimum incremental diagnostic yield for the use of advanced imaging techniques in BE surveillance. 91 In this study, experts reported a minimum incremental increase in the diagnostic yield of 27% (interquartile range, 20%-50%) for CLE before implementation in clinical practice. Furthermore, the 4 RCTs had a prevalence of dysplasia ranging from 19% to 35%, much higher than the prevalence of dysplasia in the BE population seen by most gastroenterologists at nonspecialized centers.…”
Section: Question 4: In Patients With Be Undergoing Endoscopy For Surmentioning
confidence: 69%
“…However, the question remains of what LGD means on cytology compared with LGD dysplasia on histology. The minimum incremental diagnostic yield of dysplasia for the use of WATS-3D, based on a recent survey of an international group of BE experts, 91 was 27% (95% CI, 20%-50%). Results from our SR and MA demonstrate that WATS-3D exceeds this threshold.…”
Section: Question 4: In Patients With Be Undergoing Endoscopy For Surmentioning
confidence: 99%
See 1 more Smart Citation
“…In a previous prospective study, Timmer et al used endoscopic brushings to cover larger mucosal surface and increase the biomarker yield [29]. The novel wide-area transepithelial sampling device (WATS 3D) is a promising tool, which could be combined in the future with molecular biomarkers [41,42].…”
Section: Discussionmentioning
confidence: 99%
“…Results showed the incremental diagnostic yield for virtual chromoendoscopy to be fairly low (15%, IQR 10-29%) whereas for VLE it was much higher (30%, IQR 20-50%). These results provide benchmarks that need to be met for guidelines to recommend routine use of these technologies (54).…”
Section: Incorporating Imaging Modalities Into Practice: Guidelines and Quality Indicatorsmentioning
confidence: 96%